Burkitt Lymphoma: beyond discoveries - Mbulaiteye, Sam M (BioMed Central, 2013)
First described in 1958 in Uganda, Burkitt lymphoma (BL) attracted interest worldwide following reports of its uneven geographic distribution and rapidly fatal clinical course. Both suggested infectious etiology and curability. Seminal discoveries followed in quick succession. Viral etiology – due to Epstein-Barr virus (EBV) – was confirmed. Chromosomal translocations, involving cellular MYC, a protooncogene, were discovered, shown to be a hallmark of BL, and central to the genetic basis of cancer. Cure of BL using combination chemotherapy was demonstrated. Unfortunately, civil disturbance in Africa disrupted BL research and blunted its impact on education and oncology care in Africa. Important questions went unanswered. The risk of BL due to malaria or EBV was not quantified. Efforts to answer whether BL could be prevented – by preventing malaria or early EBV infection – were abandoned. The mechanism of malaria in BL is unknown. In Africa, BL remains mostly fatal and diagnosis is still made clinically. Unprecedented advances in molecular, genomics and proteomic technologies, promising to unlock mysteries of cancers, have re-awakened interest in BL. With return of stability to Africa, the unanswered questions about BL are re-attracting global interest. This interest now includes exploiting the knowledge gained about genetics, proteomics, and bioinformatics to enable the development of targeted less toxic treatment for BL; and simpler methods to diagnose BL with high accuracy and sensitivity. The articles in the Burkitt Lymphoma (BL): Beyond Discoveries in Infectious Agents and Cancer highlight BL as priority. Authors explore etiology, pathology, pathogenesis of BL, and whether knowledge gained in the studies of BL can catalyze sustainable cancer services in one of the world’s poorest served regions.